1996
DOI: 10.1136/aim.14.2.116
|View full text |Cite
|
Sign up to set email alerts
|

Overeating: Treatment of Obesity and Anxiety by Auricular Acupuncture, An Analysis of 800 Cases

Abstract: Auricular acupuncture (placement of press needles) was applied at the stomach point (according to Nogier) and sometimes at the point of psychological balance (Shenmen) for the control of anxiety and for help in weight loss in 800 patients over a two year period. Press needles were inserted and left in for 10 to 15 days at the auricular acupuncture point and resited again after 4 to 5 days. At the same time, instructions were given for the standard treatment of obesity (information leaflet, low calorie diet, ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…While the majority of studies have focused on acupuncture's analgesic properties (e.g., Levine, Gormley, & Fields, 1976), or its use in treating physiological conditions, needle acupuncture is widely recognized by practitioners and researchers as a potent means of inducing a sense of calm and tranquility. In clinical practice, needle acupuncture is frequently used as either a sedative or an anti-anxiety agent depending upon the length of time the needles remain in place (Apostolopoulos & Karavi, 1996;Lo & Chung, 1979;Roccia & Rogora, 1976). This tranquilizing potential of acupuncture is consistent with the concept that the stimulation of acupoints in the meridian-based therapies can lead to deep relaxation and, if desired, to subsequent desensitization.…”
Section: Meridian-based Desensitizationmentioning
confidence: 98%
“…While the majority of studies have focused on acupuncture's analgesic properties (e.g., Levine, Gormley, & Fields, 1976), or its use in treating physiological conditions, needle acupuncture is widely recognized by practitioners and researchers as a potent means of inducing a sense of calm and tranquility. In clinical practice, needle acupuncture is frequently used as either a sedative or an anti-anxiety agent depending upon the length of time the needles remain in place (Apostolopoulos & Karavi, 1996;Lo & Chung, 1979;Roccia & Rogora, 1976). This tranquilizing potential of acupuncture is consistent with the concept that the stimulation of acupoints in the meridian-based therapies can lead to deep relaxation and, if desired, to subsequent desensitization.…”
Section: Meridian-based Desensitizationmentioning
confidence: 98%
“…66 However, a critical review 80 found most trials to be descriptive, of short duration (12 weeks or less), and designed using nonstandard treatment protocols. A study of 800 patients receiving auricular acupuncture 81 found significant weight loss in 64.8% of participants after 3 months, and in 35.5% after 6 to 12 months.…”
Section: Acupuncture For Reducing Ad Side Effectsmentioning
confidence: 99%
“…According to Young [9] the first time Internet addiction introduced was in 1996 by the Annual Meeting of the American Psychological Association among both academicians and clinicians. However, the definition of addiction has moved beyond this to include a number of interactive concepts, such as gambling addiction [15], video game playing [16], overdoing [17], love relationships [18], and television viewing [19]. Internet addiction is defined as, "an individual's inability to manage his or her use of the Internet, which finally results social, psychological, school, and/or work difficulties in a person's life" [20].…”
Section: Introductionmentioning
confidence: 99%